Twin Block and Its Modifications - Jeenu Raj1 , M.S Kannan2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Twin block, one of the most commonly used functional appliances has many advantages over other functionalappliances like comfort, esthetics and function. But using the same appliances for all clinical situationslimited its use in various cases. To overcome such limitations of twin block appliance, various researchershave come up with various modifications. This article gives an overview of the different modifications oftwin block appliance.